Programa de Matemtica Ruatics y la capacidad de solucin de problemas en estudiantes del 2do grado de la I.E. Mara Negrn Ugarte de Trujillo en el 2016 - Chavez Ulloa, Smilder Jos (2017)
Our research had as purpose to determine that the application of the mathematical program learning routes applying information and communication technologies "RUATICS" improves the problem solving ability in the second year students of the secondary level of the I.E. "Maria Negrn Ugarte", of the city of Trujillo in the year 2016._x000D_ The sample, subject of investigation was formed by 48 students; 24 students from the "E" section correspond to the experimental group and 24 students from the "F" section correspond to the control group. As the type of research was quasi experimental with pretest and post-test. After applying the "RUATICS PROGRAM" the results obtained demonstrate that the students of the second grade of the experimental group, achieved a significant improvement in problem solving ability.